2019
DOI: 10.1007/s11517-019-01958-3
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of heart rate variability and salivary cortisol for stress response identification based on adverse childhood experience

Abstract: Adverse childhood experiences has been suggested to cause changes in physiological processes and can determine the magnitude of the stress response which might have a significant impact on health later in life. To detect the stress response, biomarkers that represent both Autonomic Nervous System (ANS) and Hypothalamic-Pituitary-Adrenal (HPA) axis is proposed. Among the available biomarkers, Heart Rate Variability (HRV) has been proven as a powerful biomarker that represents ANS. Meanwhile, salivary cortisol h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…One recent study demonstrated the effectiveness of HRV in conjunction with salivary cortisol in assessing stress levels. They claimed that the robustness of this method renders it a potential indication of future health [30]. Another study indicated that reduced HRV with higher psychological distress and increased salivary cortisol levels were observed in patients with temporomandibular disorders [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study demonstrated the effectiveness of HRV in conjunction with salivary cortisol in assessing stress levels. They claimed that the robustness of this method renders it a potential indication of future health [30]. Another study indicated that reduced HRV with higher psychological distress and increased salivary cortisol levels were observed in patients with temporomandibular disorders [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In several previous studies, it has been reported that salivary oxytocin and cortisol levels both increased after tasks that induce stress [ 42 , 43 ] and cortisol-induced oxytocin secretion is also believed to be a part of the mechanism of stress processing [ 44 ]. Cortisol concentration in saliva and the variability of heart rate are meaningful biomarkers for assessing physiological and psychological stress as well as arousal states in humans [ 45 , 46 ]. Thus, the results of the present study suggest the existence of a physiological mechanism by which the stimuli of interactions with cats arouse the physiological state of their owners, thereby increasing oxytocin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that greater HRV reflects better psychosocial adjustment in the childhood population [11,12]. Children with behaviour problems display lower HRV [13,14], however, we do not have enough evidence about the differential effectiveness that, regarding age, a biofeedback training programme based in breath pacing, may have on children from 7 to 11 years old in Primary Education. In order to offer a comprehensive theory on children's capacity for self-regulation through biofeedback programmes, the Polyvagal Theory should be mentioned.…”
Section: Introductionmentioning
confidence: 88%